ON CONSTITUTIONAL AND LEGAL REHABILITATION OF THE MESKHETIAN TURKS: A POLITICO-LEGAL ASPECT - A. O. Usmanov (Гуманитарные и юридические исследования)
The problem of rehabilitation of people repressed in the Soviet times has not lost its importance up to this day. Until now, the issue of legal rehabilitation of some peoples deported in the 40s from the territory of Transcaucasia remains unresolved.The article examines the problem of rehabilitation of Meskhetian Turks in the context of Russian and Georgian legislation, analyzes some normative legal acts, their significance and the results of practical implementation. The regulatory legal regulation of the issue of the unreached repatriation of Meskhetian Turks to their historical homeland is considered in its development in the conditions of the USSR and in modern times. The politico-legal features of the problem under investigation in Russia are touched upon, as well as Georgia's unwillingness to actively participate in the return of the deported population from its territory.